O PROERD funciona? Notas a partir de estudo quase-experimental - Marcos Rolim; Daiana Hermann; Camila Louis Oliveira (Ciências Sociais Unisinos)
The objective of the article is to discuss the efficiency of the Drug and Violence Resistance Program (PROERD), implemented in all Brazilian states by the Military Police. The research methodology, carried out in 2018, is a quasi-experimental, self-report study, which included the selection of two groups of students from a municipal school in Porto Alegre: an intervention group with students who had participated in PROERD in 2015 and 2016 and a control group with students of the same age group who had not attended it. We found that participation in PROERD did not have any preventive effect on drug use or impact on school performance. The study showed, however, that other independent variables, such as not living with parents, not having a good relationship with them, having suffered physical violence, having been humiliated or threatened in the school environment and living with a family member who consumes alcoholic beverages, are correlated significantly with drug use and poor school performance, which suggests that they may be predictive factors for these phenomena. Empirical studies measuring results in the area of public security are still rare in Brazil, a circumstance that adds value to this work. The evidence found by the study, moreover, may be important for the definition of public policies in the area.